Aplikasi Android Untuk Backup dan Sinkronisasi File Menggunakan Amazon Web Services Simple Storage Service - Brian Stanley; Henry Novianus Palit; Agustinus Noertjahyana (Jurnal Infra, 2019)
Cloud storage technology is a solution for the local storage which consumes lot of time for maintaining in the customer’s side. Amazon Web Service (AWS) provides S3, a storage that can be used for data backup purposes, but to use its features everytime users need to login through web browser. A solution to ease the use of S3 features is to utilize a mobile app that could automate the data backup and restore process.To solve the problem of unstable connection causing file transfers to start from the beginning each time, AWS provides an API that allows resumable uploads. TransferUtility from AWS will automatically issue a resume operation on the failed upload. Test results conclude that AWS S3 have a comparable connection to other cloud storage providers such as Google Drive, Dropbox, and OneDrive. The strength of S3 is its ability to automatically resume failed transfers caused by an unstable internet connection.